Molecular mechanism and research progress on pharmacology of ferulic acid in liver diseases - Shi, Yingying; Shi, Lu; Liu, Qi; Wang, Wenbo; Liu, YongJuan (Frontiers in Pharmacology, 2023)
Ferulic acid (FA) is a natural polyphenol, a derivative of cinnamic acid, widely found in Angelica, Chuanxiong and other fruits, vegetables and traditional Chinese medicine. FA contains methoxy, 4-hydroxy and carboxylic acid functional groups that bind covalently to neighbouring adjacent unsaturated Cationic C and play a key role in many diseases related to oxidative stress. Numerous studies have shown that ferulic acid protects liver cells and inhibits liver injury, liver fibrosis, hepatotoxicity and hepatocyte apoptosis caused by various factors. FA has protective effects on liver injury induced by acetaminophen, methotrexate, antituberculosis drugs, diosbulbin B and tripterygium wilfordii, mainly through the signal pathways related to TLR4/NF-κB and Keap1/Nrf2. FA also has protective effects on carbon tetrachloride, concanavalin A and septic liver injury. FA pretreatment can protect hepatocytes from radiation damage, protects the liver from damage caused by fluoride, cadmium and aflatoxin b1. At the same time, FA can inhibit liver fibrosis, inhibit liver steatosis and reduce lipid toxicity, improve insulin resistance in the liver and exert the effect of anti-liver cancer. In addition, signalling pathways such as Akt/FoxO1, AMPK, PPAR γ, Smad2/3 and Caspase-3 have been shown to be vital molecular targets for FA involvement in improving various liver diseases. Recent advances in the pharmacological effects of ferulic acid and its derivatives on liver diseases were reviewed. The results will provide guidance for the clinical application of ferulic acid and its derivatives in the treatment of liver diseases.